1983
DOI: 10.1002/1097-0142(19830915)52:6<954::aid-cncr2820520603>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of anaplastic giant and spindle cell carcinoma of the thyroid gland with combination adriamycin and radiation therapy a new approach

Abstract: The authors have devised a new treatment regimen consisting of combination Adriamycin and hyperfractionated radiation therapy for the treatment of anaplastic giant and spindle cell carcinoma of the thyroid gland. The regimen consists of a once weekly administration of low‐dose Adriamycin (doxorubicin) (10 mg/m2) and hyperfractionated radiation therapy. The radiation therapy is carried out with fractional dose of 160 rad per treatment twice a day for three days per week. The total tumor dose is 5760 rad deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(28 citation statements)
references
References 4 publications
0
27
0
1
Order By: Relevance
“…Several of the patients included suffered from severe therapy-related toxicity (epithelitis or mucosal ulcerations in the mouth and throat) which caused interruptions of the treatment. Following a report by Kim and Leeper (1983), we replaced the BCF with weekly administered doxorubicin. In addition to weekly doxorubicin, Kim and Leeper (1983;1987) used hyperfractionated but not accelerated radiotherapy, and reported results similar to those obtained in our protocol with BCF but with less toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the patients included suffered from severe therapy-related toxicity (epithelitis or mucosal ulcerations in the mouth and throat) which caused interruptions of the treatment. Following a report by Kim and Leeper (1983), we replaced the BCF with weekly administered doxorubicin. In addition to weekly doxorubicin, Kim and Leeper (1983;1987) used hyperfractionated but not accelerated radiotherapy, and reported results similar to those obtained in our protocol with BCF but with less toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Following a report by Kim and Leeper (1983), we replaced the BCF with weekly administered doxorubicin. In addition to weekly doxorubicin, Kim and Leeper (1983;1987) used hyperfractionated but not accelerated radiotherapy, and reported results similar to those obtained in our protocol with BCF but with less toxicity. Our aim in this present study was to prospectively evaluate the treatment and change only one modality at a time; this practice will enable assessment of the various components in the multimodality treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Although ATC is relatively radioresistant, some studies have shown palliative local control in 68% to 80% of patients. 83,[87][88][89][90] The timing, dose, and mode of delivery of EBRT remain controversial. Some investigators have tried hyperfractionated radiotherapy to keep up with the rapid doubling times of ATC.…”
Section: Surgerymentioning
confidence: 99%
“…Os tumores pouco diferenciados apresentam baixa captação de iodo-131 e reduzida chance de resposta ao tratamento com iodo-131, limitando ainda mais o prognóstico quando se considera que modalidades terapêuticas como a quimio e radioterapia têm um papel extremamente limitado nestes casos (42). Pacientes com captação de iodo-131 baixa ou ausente e com evidência clínico-laboratorial de doença em progressão podem ser medicados com análogos do ácido retinóico, utilizados na tentativa de reduzir a taxa de crescimento e promover uma rediferenciação celular no tumor.…”
Section: áCido Retinóicounclassified